Il palazzo in mezzo a una selva millenaria / The palace in the middle of a thousand-year old forest Villa Borbone a Viareggio: progetto di conoscenza / Bourbon Villa in Viareggio: knowledge and conservation project - CACCIA GHERARDINI, SUSANNA (Ricerche. Architettura, Pianificazione, Paesaggio, Design, 2022)
Villa Borbone show up to the eye of the attentive traveler immersed in the geometries of a lush garden, fading into the motility of the coastal landscape. A set of buildings, including the small chapel steeped in classical suggestions, is a part of what once constituted the vast property of the ducal family. An incredibly precious heritage, which this book aims to account for, restoring its history, its materiality, but also all its fragility, in an attempt to define a path that can contribute to its preservation.